Forecasting The Number of Aircraft Passengers Arriving Through Soekarno-Hatta Airport Using Arima Model - Windi Marnizal Putri; Fauziah Nur Fahirah Sudding (Journal of Actuarial, Finance, and Risk Management, 2022)
Soekarno-Hatta International Airport is well known as the busiest airport in Indonesia with the number of airplane passengers normally grow from year to year. In 2010, there were more than 43 million passengers, and had increased up to 62.4 million over the year 2011. Risk of overcapacity became an issue. Thus, in the following year, the airport was planned for an expansion. Predicting the frequency of passengers can be helpful for future planning and to improve airport facilities and policy. This research used Autoregressive Integrated Moving Average (ARIMA) to forecast the number of aircraft passengers. ARIMA (0,1,1) is the most suitable model used with MAPE 110%, the results is 2,405,205 passengers. Actual data and predictive data are not much different